Calculated vs. Experimental Values for Volume and Surface Resistivity in Various Polymer Compounds - Megan Webster (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
Versatile due to their resistance to high stress environments including but not limited to extreme temperature, pressure, and stress, polymers additionally have many uses in electrical applications wherein antistatic or conductive properties are preferential, i.e. conductive seals, oil pipeline spheres, and gaskets, to name a few. Being a complex material, many factors may affect the electrical resistivity of a given polymer compound including type and amount of carbon black, type of rubber, cure time and temperature, and dispersion, amongst other factors. External conditions such as relative humidity and temperature also play key roles. This paper will analyze five different rubber compounds by examining the difference between experimental and calculated volume and surface resistivity in both high and low humidity conditions.
Keywords: polymer compounds; electrical properties of materials; surface resistivity; volume resistivity; carbon black; bloom